2021
DOI: 10.1029/2020wr028284
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamics, Sediment Transport and Morphological Features at the Confluence Between the Yangtze River and the Poyang Lake

Abstract: Confluences are critical nodes in a river network and affect flow, sediment transport, water quality, and ecological patterns. Significant changes in hydrodynamics, bed morphology as well as environmental and ecological features occur at the confluence, where the flows from two tributaries combine and adjust to the postconfluence planform geometry. Confluence of two flows with different momentum and velocity ratios (the ratio of the variable of one channel to that of the other) often results in a downstream sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(46 citation statements)
references
References 90 publications
2
38
0
3
Order By: Relevance
“…In general, bank retreat controls the equilibrium river width by eventually reducing the shear stress on the banks to a critical threshold value (Francalanci et al., 2020; K. B. J. Dunne & Jerolmack, 2020). From the perspective of cross‐sectional evolution, bank retreat is responsible for the instantaneous adjustment of the bank line (C. Hackney et al., 2015; Darby et al., 2007), which modulates near‐bank hydrodynamics and, together with the transverse transport of sediment driven by secondary flow circulations which establish in meandering bends (Bolla Pittaluga & Seminara, 2011), gradually shift the thalweg from one bank to the other (Fryirs & Brierley, 2012; Parker et al., 2011; Stecca et al., 2017; Yuan et al., 2021). In various settings, bank‐derived materials have been reported as the dominant factor of sediment budgets (Kronvang et al., 2013; Trimble, 2009).…”
Section: Feedbacks Between Bank Retreat and Morphodynamicsmentioning
confidence: 99%
“…In general, bank retreat controls the equilibrium river width by eventually reducing the shear stress on the banks to a critical threshold value (Francalanci et al., 2020; K. B. J. Dunne & Jerolmack, 2020). From the perspective of cross‐sectional evolution, bank retreat is responsible for the instantaneous adjustment of the bank line (C. Hackney et al., 2015; Darby et al., 2007), which modulates near‐bank hydrodynamics and, together with the transverse transport of sediment driven by secondary flow circulations which establish in meandering bends (Bolla Pittaluga & Seminara, 2011), gradually shift the thalweg from one bank to the other (Fryirs & Brierley, 2012; Parker et al., 2011; Stecca et al., 2017; Yuan et al., 2021). In various settings, bank‐derived materials have been reported as the dominant factor of sediment budgets (Kronvang et al., 2013; Trimble, 2009).…”
Section: Feedbacks Between Bank Retreat and Morphodynamicsmentioning
confidence: 99%
“…As confluências fluviais produzem alterações significativas na hidrodinâmica e morfologia do leito em função do ajuste dos dois fluxos a geometria local e pós confluência (Yuan et al, 2021). A junção dos canais desencadeia anomalias dos padrões de circulação do fluxo e sedimentos no curso fluvial.…”
Section: Distribuição De Fluxo E Morfologia Em Confluência Fluvial Rochosa De âNgulo Obtusounclassified
“…A junção dos fluxos produz o poço de escavação, denominado scour hole. Yuan et al (2021) associaram a área de maior entalhamento do leito aos movimentos helicoidais do fluxo. No caso da junção do Rio das Pedras, apesar da erosão de leito no encontro dos fluxos, a maior incisão do substrato ocorre entre 80 a 140 metros da junção, constituindo um remanso no fluxo, com incisão de até cinco metros de profundidade (Figura 12).…”
Section: Distribuição De Fluxo E Morfologia Em Confluência Fluvial Rochosa De âNgulo Obtusounclassified
See 1 more Smart Citation
“…Gualtieri et al [19] demonstrated that the momentum transfers and the mixing interface width in the confluence hydrodynamic zone depend on the flow conditions. Yuan et al [20] conducted analysis of the helical motion in confluences and found that flow structures originating from circular cells affect sediment transport. Other researchers have conducted numerical simulations using the Reynolds-Averaged Navier-Stokes (RANS) model to analyze 3D flow characteristics based on field measurements and laboratory experiments [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%